1978
DOI: 10.1079/bjn19780131
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the voluntary intake and digestion of a range of forages at different times of the year by the sheep and the red deer (Cervus elaphus)

Abstract: I. Comparisons were made between castrated male Scottish Blackface sheep and red deer (Cervus eluphus) of voluntary forage intake (VFI), digestibility and the mean retention time (MRT) of a particulatephase markel ('OSRu-phenanthro1ine) in the alimentary tract, when a range of forages: dried-grass pellets, chopped dried grass, fIesh-frozen Agrosris-Festucu spp. and heather (Cullunu vulgaris, L. Hull) were given at different times of the year.2. On both the dried-grass-pellet and chopped dried-grass diets the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2
11

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 14 publications
4
97
2
11
Order By: Relevance
“…Ingestion of a high-fiber food (i.e. mature oat hay) during the exposure period may have increased reticulo-rumen capacity in EL (Milne et al, 1978;Distel and Provenza, 1991), which may have contributed to their increased acceptance of LQF.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of a high-fiber food (i.e. mature oat hay) during the exposure period may have increased reticulo-rumen capacity in EL (Milne et al, 1978;Distel and Provenza, 1991), which may have contributed to their increased acceptance of LQF.…”
Section: Discussionmentioning
confidence: 99%
“…Rumen capacity has been proposed to limit VFI of ruminants consuming forage diets (Black, 1990), and it has been suggested that red deer may be able to increase rumen capacity during summer thus accommodating their seasonal increase in VFI (Milne et al 1978;Milne, 1980). However, results of the present study showed that rumen capacity remained relatively constant, and that one mechanism used by red deer to increase VFI was to increase rumen pool size as a proportion of total capacity.…”
Section: Discussionmentioning
confidence: 99%
“…, 1985). High VFT is associated with increasing daylength (spring-summer) and low VFI is associated with decreasing daylength (autumn-winter;Milne et al 1978; Suttie ef al. 1984;Domingue, 1989).…”
Section: ~~~ ~~mentioning
confidence: 99%
See 1 more Smart Citation
“…Although one usually considers mixed-species stocking to refer to two or more of the predominant domestic ruminant livestock species (Ralphs et al, 1986;Abaye et al, 1994;del Pozo et al, 1998;Animut et al, 2005a and2005b;Celaya et al, 2007;Sanon et al, 2007), wildlife if present should be considered as part of the mix (Grelen and Thomas, 1957;Milne et al, 1978;Bryant et al, 1979;Campbell and Johnson, 1983;Bastian et al, 1991;Gallina, 1993;Didier et al, 1994;Kreuter andWorkman, 1996 andVavra, 2005;Williams and Haynes, 2006;Anderson and McCuistion, 2008). Although not specifically addressed in this paper, the addition of wildlife to the species mix can create additional management challenges and economic opportunities from both ecotourism (Georgiadis et al, 2007) and sport hunting or game cropping (Denney, 1972;Demarais et al, 1990).…”
Section: Introductionmentioning
confidence: 99%